Renal Transplant Survey: how standardised is a standard kidney transplant? - Wicht, Jonathan H (Department of Surgery, 2017)
Aim: The primary intention of the current study was to discover if there are international standards in renal transplantation. Method: A questionnaire was created using an online survey tool (Qualtrics ®), and distributed to a list of email addresses supplied by the unit's senior transplant surgeon. A literature review was performed on the questions and on the history of transplantation. Ethics was approved by FHS HREC number 193/2015. Results: A total of 30 surveys were completed from a total of 147 emails sent (20.4%). Two thirds of respondents work exclusively in the public sector and almost two-thirds (63.3%) of the respondents had been involved in transplantation for over 10 years. Two thirds of the surgeons estimate that their units perform more than 60 transplants per annum. Only 30% (9/30) use living donors in more than 50% of their surgeries. Most (53.3%) perfuse the kidneys both in the donor (in situ) and outside (ex situ or ex vivo). If no anatomic abnormalities were noted in open living donor nephrectomy, 63.3% would prefer to use the left kidney, and the recipient transplantation would be performed on the right side (76.7%). The majority (90%) of surgeons would preserve the vas deferens, but sacrifice the round ligament and inferior epigastric vessels (76.7% and 80% respectively). There is no marked difference for use of either the internal or external iliac artery for the arterial anastomosis, but most use the external iliac vein for venous anastomosis (86.7%). 80% use a ureteroneocystostomy with a tunnel, and 60% use a DJ stent or ureteric catheter and closed suction drain routinely. Two thirds would remove the transurethral catheter on day 4-7 post operatively. 80% routinely biopsy the kidney, and 63.3% would biopsy prior to treating for possible acute renal rejection. Discussion: These results compare with some of the studies found in the literature and operative textbooks. There do appear to be standards noted between most of the respondent's answers. Conclusion: There do appear to be standards for renal transplantation and these are appreciated globally.